Analysis of Naturally Hospitable Alternative Energy Cultivation Regulations - Siregar, Ramlan; Zulkarnain, Zulkarnain; Siregar, Iskandarsyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research discusses Alternative Energy Cultivation Regulations in Overcoming the Energy Crisis, which are discussed from International Relations. In formulating national regulations that include foreign policy, energy is one of the issues discussed because it is related to many people's lives. The energy potential will significantly influence Indonesia's foreign policy. Energy plays a critical role because energy is the driving force for a country's economic sector. Increased cultivation will increase the need for energy as well. Countries that control energy will become strong and superpower. Indonesia is very concerned about the issue of energy supply security given the increasing energy consumption in Indonesia, the scarcity of energy supplies, and the tendency of rising energy prices. This condition is exacerbated because almost a quarter of the domestic oil demand must be imported from other countries. Therefore, Indonesia must find the most appropriate way to ensure the availability of naturally hospitable energy. The research method is a qualitative descriptive method. The conclusion drawn from this research is the interdependence of all world energy actors.Â